Träd och trä: Materialitet och diffraktion i Eva Ströms poesi - Käck, Elin (Tidskrift för litteraturvetenskap, 2025)
Trees and wood. Materiality and Diffraction in Eva Ström’s Poetry Eva Ström’s poetry in Utskuret ur ett större träd (2013) and Jag såg ett träd (2022) frequently includes references to trees. This article examines how Ström’s poetry negotiates the boundaries between humans, nature, materiality, and aesthetics. It also suggests that Ström’s poetic method can be seen in light of Karen Barad’s concept of diffraction, as it invites us to read phenomena of various kinds and scales through one another. Ström’s poetry collections share certain features, such as the preoccupation with trees and contemporaneous news, including disasters and extreme weather. Taken together, they also focus on the sculptural, art history, medicine, and religious rituals. The latter collection details the Covid-19 pandemic, which foregrounds interconnectivity and the difficulty of maintaining a separation between the human body and the environment, something which posthuman materialist criticism has long recognized. In addition, the emphasis on deep time brought on by the invocation of dendrology emplaces the human in a larger, geological time frame. Similar concerns likewise emerge in the previous collection. The question of where a human begins or ends is asked, which reverberates with the later collection’s preoccupation with porosity, interconnectivity, and enmeshment. With its blurring of foreground and background, Ström’s poetry emerges as a poetics of diffraction, reading events and occurrences through one another, ranging from materials to religious artefacts, current news items, art works, and the quotidian. With its emphasis on trees, sculptures, art, and religious rituals, her poetry foregrounds material and posthuman concerns, but these are always paired with—troubled by just as they themselves in turn trouble—older, humanistic understandings of what it means to be human.